The Law of Adopting Children in Islamic Fiqh and the Compilation of Islamic Law - Ramadhanti, Maghfirah Nur; Satrianingsih, Andi; Basri, St Risnawati (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
This research aims to understand the law of adopting children in Islamic Jurisprudence and the law of adopting children in the Compilation of Islamic Law. This type of research is library research with a qualitative approach. The primary data sources used in this research are Islamic jurisprudence books and the Compilation of Islamic Law (KHI). Meanwhile, secondary data sources are books, journals and textbooks that are related to what the author discusses. The data collection technique in this research is documentation. Then analyzed using content analysis techniques. The results of this research are that adoption in Islamic jurisprudence is prohibited if the adopted child's lineage is attributed to his or her adoptive parents. Because Islamic jurisprudence scholars agree that a child's fate is determined by three things, namely a valid marriage, a fasid marriage, and wathi' syubah. However, adopting a child with the aim of caring for, nurturing and educating with love without changing the child's lineage is a commendable act and is a pious deed recommended by the Islamic religion. In Islamic jurisprudence, adopted children do not inherit from their adoptive parents, but can only obtain property from their parents through a gift or will and their adoptive parents cannot act as guardians for their marriage. Apart from that, adopted children are not mahram to their adoptive parents, so they must pay attention to the boundaries in interacting between the two. As for the adoption of children in the Compilation of Islamic Law, it is permissible, provided it is limited to transferring responsibility from the child's parents to the adoptive parents. This transfer of responsibility includes paying for daily living, caring for him with love and fulfilling all his needs, without changing the child's fate. Apart from that, adopted children do not become heirs of their adoptive parents, but have the right to obtain a mandatory will as regulated in article 209 and adoptive parents do not have the right to become marriage guardians for their adopted children